The Neural Mechanisms of Social Learning from Fleeting Experience with Pain - Fan, Yang-Teng; Chen, Chenyi; Cheng, Yawei (Frontiers in Behavioral Neuroscience, 2016)
Social learning is critical for humans to adapt and cope with rapidly changing surroundings. Although neuroscience has focused on associative learning and pain empathy, the neural mechanisms of social learning through fleeting pain remains to be determined. This functional MRI study included three participant groups, to investigate how the neuro-hemodynamic response and subjective evaluation in response to the observation of hand actions were modulated by first-hand experience (FH), as well as indirect experience through social-observational (SO) and verbal-informed (VI) learning from fleeting pain. The results indicated that these three learning groups share the common neuro-hemodynamic activations in the brain regions implicated in emotional awareness, memory, mentalizing, perspective taking, and emotional regulation. The anterior insular cortex (AIC) was commonly activated during these learning procedures. The amygdala was only activated by the FH. Dynamic causal modeling further indicated that the SO and VI learning exhibited weaker connectivity strength from the AIC to superior frontal gyrus than did the FH. These findings demonstrate that social learning elicits distinct neural responses from associative learning. The ontogeny of human empathy could be better understood with social learning from fleeting experience with pain.